Orgasmic behavior and the frequencies of sexual function disorders in 398 postpartum women in Istanbul - Sayın, Ümit; Kocatürk, Asiye (Wiley-Blackwell, 2015)
Introduction: Very few studies are realized on the orgasmic behavior and the distribution and frequencies of sexual function disorders (SFD) in Turkish women. The authors started a series of surveys, named as İstanbul Report (IR) on Female Sexuality. This study was a subgroup of the survey series of IR. Methods: The survey was realized among the post-partum women after their giving births in various hospitals in İstanbul. 58 questions were asked about the sexual behavior and other related family problems of the post-partum women. 398 responses were collected and analyzed in SPSS. The education distribution in the group was: Elementary: 29 %; High School: 53.4 %; University: 16.6 %; MSc &PhD: 0.8 %. Results: 1) Among the 398 post-partum women, the SFD frequency encountered at least once (or more) in their entire lives was 42.3 %, while the most common specific SFDs were as : Vaginismus: 10.3 % ; Dyspareunia: 12.8 %; Anorgasmia: 14.2 %; Lack of sexual interest: 6.8 %; Lubrication problems during intercourse: 2.5 %. 2) 66 % of the group stated that they experienced orgasms, always or generally or sometimes in their sexual relations with their husbands. 68.2 % of them experienced clitoral orgasms always or generally or sometimes; while coital-vaginal orgasm frequency was 17.9 % (always) and 11.3 % (generally). 47.8 % stated that they never or rarely or sometimes experienced coital-vaginal orgasms. 32.3 % of the group experienced only ONE orgasm at each love making, while 47.9 % said they experienced orgasms between 2-10. Conclusion: Vaginismus, anorgasmia, dyspareunia, lack of sexual interest, orgasm difficulties are the most common and increasing SFDs in Turkey. Experiencing coital-vaginal orgasms is also very low in Turkey. Sexual education to the public at the high schools and universities should be planned by the government or privately in Turkey. POSTER TEXT: Introduction: There are not many reports about the sexual and orgasmic behavior of Turkish women. Our group has made some surveys and still continuing other surveys (such as İstanbul Report) about the orgasmic behavior of the female population in Turkey. Anorgasmia, Dyspareunia and Vaginismus are the common sexual function disorders among Turkish females. According to the surveys we have done, nearly 14 to 20 % of educated and middle class women in Turkey suffer anorgasmia; vaginismus has also become a serious sexual problem during the last 20 years, while 9 to 13 % of Turkish women suffer from vaginismus1. In this survey, which was a part of İstanbul Report, we have investigated the sexual behavior of women among 398 postpartum women. Methods: The survey was realized among the post-partum women after their giving births in various hospitals in İstanbul. In the survey there were 58 questions about the sexual behavior and other related family problems of the post-partum women. 398 responses were collected and analyzed in SPSS. The education distribution in the group was: Elementary: 29 %; High School: 53.4 %; University: 16.6 %; MSc &PhD: 0.8 %. Minimum age was 18; maximum age was 64. The average of ages was 32.607 ± 8.3 (S.D). The age distribution is given at the below plot. Conclusion: Vaginismus, anorgasmia, dyspareunia, lack of sexual interest, orgasm difficulties are the most common and increasing SFDs in Turkey; even in the group of post-partum women who have had healthy sexual lives, the incidence of former experienced vaginismus, anorgasmia and decreased libido was higher than the expected. Compared to global findings, experiencing coital-vaginal orgasms is also very low in Turkish women. The tendency of increased SFDs occurred during the last 20 years and it seems that there is an alteration and transformation of female sexual response in the Turkish population. This consequence can be mostly because of the cultural, political, and governmental attitudes which may have changed the sexual behaviors, belief and moral systems and the visions of the Turkish males and females. Besides because of the cultural and political attitudes there is not much sexual education in the Turkish society. Sexual education given to the public at the high schools and universities should be planned by the government or privately in Turkey to overcome exploding sexual problems and SFDS.
WOS: 000352790600228
Keywords: Orgasmic; Postpartum; Function